2002
DOI: 10.3354/dao049117
|View full text |Cite
|
Sign up to set email alerts
|

Segment 8 encodes a structural protein of infectious salmon anaemia virus (ISAV); the co-linear transcript from Segment 7 probably encodes a non-structural or minor structural protein

Abstract: In this study we present the cloning, expression and partial identification of Genomic Segment 7 of infectious salmon anaemia virus (ISAV). The nucleotide sequence corresponding to Segment 7 was isolated from a bacteriophage lambda cDNA library and contained 2 overlapping open reading frames (ORFs) of 903 and 522 bases respectively. It also contained an ISAV-specific conserved nucleotide motif in the mRNA 5' region. The co-linear transcript representing the large ORF undergoes a splicing event that removes a 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
35
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 19 publications
3
35
0
Order By: Relevance
“…The most conserved proteins between ISAV and influenza virus A/PR/8/34 are PB1 proteins although they share only 31 % amino acid similarity. 59-RACE amplification confirmed the production of a spliced mRNA from segment 7 mRNA ORF1 that encodes the S7 ORF2, as previously published (Bierin et al, 2002; Ritchie et al, 2002) (data not shown). It is to be noted that the ISAV segment 7 ends, previously published by Sandvik et al (2000), were found to be segment 6 ends.…”
supporting
confidence: 58%
See 2 more Smart Citations
“…The most conserved proteins between ISAV and influenza virus A/PR/8/34 are PB1 proteins although they share only 31 % amino acid similarity. 59-RACE amplification confirmed the production of a spliced mRNA from segment 7 mRNA ORF1 that encodes the S7 ORF2, as previously published (Bierin et al, 2002; Ritchie et al, 2002) (data not shown). It is to be noted that the ISAV segment 7 ends, previously published by Sandvik et al (2000), were found to be segment 6 ends.…”
supporting
confidence: 58%
“…Segment 8 produces an mRNA transcript containing two overlapping ORF. The smaller ORF1 encodes the matrix protein (M) and the S8 ORF2 was recently shown to be involved in the modulation of type I IFN response together with S7 ORF1 (Bierin et al, 2002;Garcia-Rosado et al, 2008).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The ISAV genome is composed of eight negative-sense, single-stranded RNA segments, and while nucleotide sequences of all segments have been published (9,43,44,56,66,67,74,75), much remains to be elucidated with respect to protein identification and characterization. A total of 12 proteins have been detected by immunoprecipitation of lysates from radiolabeled infected cells (40), while four major structural proteins have been recognized in purified ISAV particles, including the matrix (M1; 22 to 24 kDa) (7,24), the nucleoprotein (NP; 66 to 71 kDa) (3,24), and two membrane glycoproteins (24). The receptor-binding and receptor-destroying activities are associated with the 42-kDa glycoprotein encoded by segment 6, termed the hemagglutininesterase (HE) (24,25,34,42,43,66), while the activities of the second glycoprotein, glycoprotein 50 (gp50), encoded by segment 5 (9), have not been described previously.…”
Section: Infectious Salmon Anemia Virus (Isav) Is An Enveloped Virusmentioning
confidence: 99%
“…Like the influenza A and B viruses, ISAV has a negative-sense RNA genome with eight gene segments that express a total of 10 polypeptides. The smallest segment, segment 8, has two overlapping colinear ORFs that respectively encode two proteins M1 and M2, with M1 being the viral matrix protein with a molecular weight of ∼22 kDa (24). As expected, ISAV M1 is expressed late during infection and accumulates in both nucleus and cytosol (25,26).…”
mentioning
confidence: 93%